1981
DOI: 10.1111/j.1478-4408.1981.tb03570.x
|View full text |Cite
|
Sign up to set email alerts
|

Physico–chemical and Dyeing Properties of Disperse Dyes containing Phthalimide Residues

Abstract: The relationship between the constitution and the physico–chemical and dyeing properties of disperse dyes containing phthalimide residues has been studied. The influence of the –NH or –NCH3 group in the phthalimide residues on the thermal and spectral properties of dyes has been investigated. Their influence on the dyeing process and on the colour and fastness properties of dyed polyester have also been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Phthalimidylazo disperse dyes first appeared as the subject of patents over 30 years ago [18,19] and have also formed the basis for claims over the last few years [20–22] concerning good fastness and dyeability on polyester. While industry has exploited their chemistry commercially [23], little has appeared in the academic literature concerning their colour and application properties and that which has been published features examples with relatively simple structures [24–27].…”
Section: Introductionmentioning
confidence: 99%
“…Phthalimidylazo disperse dyes first appeared as the subject of patents over 30 years ago [18,19] and have also formed the basis for claims over the last few years [20–22] concerning good fastness and dyeability on polyester. While industry has exploited their chemistry commercially [23], little has appeared in the academic literature concerning their colour and application properties and that which has been published features examples with relatively simple structures [24–27].…”
Section: Introductionmentioning
confidence: 99%
“…Papers by J. Szadowski et al reported the results of studies of adsorption of azobenzene dyes, containing amido groups [5], and naphthylamine derivatives [6] on polyester fibres and films in water dyebath. Evaluated parametes of LogP with experimental partition coefficients between polyester and dyebath in logarithmic scale exhibits rather good correlation [7].…”
Section: Resultsmentioning
confidence: 99%